2020
DOI: 10.1074/jbc.ac119.010924
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo study of the impact of deficiency in the DNA repair proteins PAXX and XLF on development and maturation of the hemolymphoid system

Abstract: Repair of DNA double-strand breaks by the nonhomologous end joining pathway is central for proper development of the adaptive immune system. This repair pathway involves eight factors, including XRCC4-like factor (XLF)/Cernunnos and the paralog of XRCC4 and XLF, PAXX nonhomologous end joining factor (PAXX). Xlf−/− and Paxx−/− mice are viable and exhibit only a mild immunophenotype. However, mice lacking both PAXX and XLF are embryonic lethal because postmitotic neurons undergo massive apoptosis in embryos. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Previously, we showed that mice lacking XLF, PAXX and p53 were live-born and had nearly no B and T cells, reduced size of spleen and hardly detectable thymus [20] (Figure 5). Consistent with this model, a conditional AGING knockout mouse model, which results in doubledeficiency of XLF/PAXX in early hematopoietic progenitor cells, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [33]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [33].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previously, we showed that mice lacking XLF, PAXX and p53 were live-born and had nearly no B and T cells, reduced size of spleen and hardly detectable thymus [20] (Figure 5). Consistent with this model, a conditional AGING knockout mouse model, which results in doubledeficiency of XLF/PAXX in early hematopoietic progenitor cells, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [33]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [33].…”
Section: Discussionmentioning
confidence: 65%
“…Consistent with this model, a conditional AGING knockout mouse model, which results in doubledeficiency of XLF/PAXX in early hematopoietic progenitor cells, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [33]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [33]. Our new data provide evidence that Xlf -/-Paxx -/-Trp53 +/and Xlf -/-Paxx -/-Trp53 -/mice possess a very small number of mature B cells in the spleen and bone marrow, as well as very minor fractions of single positive T cells in thymus and spleen (Figures 2, 5 and Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 65%
“…Consistent with this model, a conditional knockout mouse model, which results in doubledeficiency of XLF/PAXX in early hematopoietic progenitor cells, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [32]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [32].…”
Section: Discussionmentioning
confidence: 69%
“…Consistent with this model, a conditional knockout mouse model, which results in doubledeficiency of XLF/PAXX in early hematopoietic progenitor cells, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [32]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [32]. Our new data provide evidence that Xlf -/-Paxx -/-Trp53 +/and Xlf -/-Paxx -/-Trp53 -/mice possess a very small number of mature B cells in the spleen and bone marrow, as well as very minor fractions of single positive T cells in thymus and spleen ( Figure 2, 5 and Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 69%
“…6). Moreover, a conditional knockout mouse model, which results in double-deficiency of XLF/PAXX in early hematopoietic progenitor cells only, was also able to overcome the embryonic lethality of Xlf -/-Paxx -/mice [37]. With this model, impairment of V(D)J recombination in Xlf -/-Paxx -/cells, as well as the resulting depletion of mature B cells and lack of a visible thymus could also be observed in vivo [37].…”
Section: Discussionmentioning
confidence: 99%